Problem Metodologis dalam Studi Hukum Islam - Solikhin, Iin (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
The effort to apply God’s revelation creates a dispute between the revelation itself and the social context. Usul fiqh as an understanding method which has divine texts as starting points is adjusted to the future and based on God’s revelation by doing ijtihad. Usul fiqh developes significantly in translating those revelation in accordance with society demand,place and condition.